1998
DOI: 10.1126/science.281.5379.917
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Literacy

Abstract: R einforced by the dismal U.S. performame on the Third International Mathematics and Science Study (TIMSS), deploring our lack of scientific literacy has become quite popular recently. By the broadest defition, more than 90% of Americans are scientifically illiteratean appalling statistic by anyone's standards and possibly a threat to our well-being. Yet with all this agreement we see astonishing ambiguity-and two different defitions of scientific literacy. The first emphasizes practical results and stresses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 0 publications
0
24
0
4
Order By: Relevance
“…18 A recent national survey of attitudes toward an understanding of science in the UK showed that for those with little scientific knowledge, medical research is judged as far more interesting and scientific than anything else, and these citizens tend to take medical research as a model for all science. 29 Science education reforms to address civic scientific literacy should focus on what the public wants to know, for example, using randomized clinical trials to illustrate the scientific method and the difference between controlled experiments and observations.…”
Section: Discussionmentioning
confidence: 99%
“…18 A recent national survey of attitudes toward an understanding of science in the UK showed that for those with little scientific knowledge, medical research is judged as far more interesting and scientific than anything else, and these citizens tend to take medical research as a model for all science. 29 Science education reforms to address civic scientific literacy should focus on what the public wants to know, for example, using randomized clinical trials to illustrate the scientific method and the difference between controlled experiments and observations.…”
Section: Discussionmentioning
confidence: 99%
“…La alfabetización científica ha estado presente en la educación sobre problemáticas relevantes de la sociedad, apoyando la participación ciudadana en la toma de decisiones que le competen y fomentando el pensamiento crítico y creativo sobre el mundo natural (Maienschein, 1998). Un ejemplo claro de materias en que la sociedad debe tener injerencia es el uso de fertilizantes químicos y pesticidas para combatir insectos, plagas, malezas y hongos.…”
Section: De La Potencialidad a La Realidad Aspectos Generales E Históunclassified
“…En Chile sucede algo similar, ya que temas de salud como la píldora del día después, el aborto terapéutico o las vacunas han significado conflictos entre científicos y agrupaciones que se oponen a las acciones ligadas a ellos, lo que ha impedido que se legisle rigurosamente en estos ámbitos.que afecte la vida debería ser un proceso del que forme parte una sociedad con conocimiento científico, que le permita decidir adecuadamente y distinguir entre afirmaciones fiables y sin fundamentos y aquellas con validez comprobable (Maienschein, 1998).…”
Section: De La Potencialidad a La Realidad Aspectos Generales E Históunclassified
“…XVIII 1 organizaciju nastave i način procene naučenog. Postoji predlog da se razlikuju dva termina (Maienschein, 1998): pismenost u nauci (science literacy) i naučna pismenost (scinetific literacy), pri čemu bi se prvi odnosio na konkretna znanja iz nauke (pojmove, teorije, zakone), a drugi na naučni pogled na svet i na sticanje naučnog znanja, razvoj kritičkog mišljenja i usvajanje naučnih vrednosti i morala. Ovaj drugi pristup traži više vremena, orijentisan je na pitanja, a ne na odgovore i teško ili nemoguće ga je meriti klasičnim testovima znanja.…”
Section: šTa Je Naučna Pismenost?unclassified